Inventarisasi Tumbuhan Lumut Di Kawasan Air Potang-Potang Negeri Itawaka Kabupaten Maluku Tengah - Kevin Tamaela; Gledys Sopacua; Pricilia Sopratu; Kalsum Selehulano (Peneliti.net, 2020)
This study aims to determine the inventory of moss plants in the area of ​​Air Potang-Potang, Itawaka Village, Saparua Timur District, Maluku Tengah Regency. This research was conducted in the Air Potang-Potang, Itawaka Village area. The research method used is an exploratory survey method. The identification results of the types of mosses found 6 types, consisting of 3 types of liverworts, namely Marchantia polymorpha L., Dumortiera hirsute, Conocephalum conicum and 3 types of leaf moss, namely Bryum argenteum, Leucobryum glaucum, Dicranum scoparium.